Effect of the Ratio of Shrimp Waste Powder (Fenneropenaeus merguiensis de Man) to Glycerol on the Characteristics of Yam Starch-Derived Bioplastics - Ulyarti; Adisty Ramadhani; Mursyid; Nazarudin (Jurnal Penelitian Pendidikan IPA, 2025)
Yam starch-based bioplastics generally exhibit low mechanical properties. However, the addition of shrimp waste powder has been shown to improve the tensile strength and elongation of yam starch bioplastics, with the enhancement occurring within an optimal range. Glycerol, on the other hand, is known to affect bioplastic properties in a dose-dependent manner. This study was conducted to investigate the effects of shrimp waste powder and glycerol ratios on the characteristics of yam starch-derived bioplastics.  A Completely Randomized Design (CRD) was used, consisting of five treatment levels with three replications. The treatment levels were shrimp waste powder to glycerol ratios of 0:3, 0.5:2.5, 1:2, 1.5:1.5, and 2:1. The results showed that the shrimp waste powder to glycerol ratio significantly affected the tensile strength, elongation, thickness and water vapor transmission rate (WVTR) of the bioplastics, but had no significant effect on water absorption.  The biodegradability of bioplastic in soil ranged from 144 to 149 days.   The best treatment was 1:2 ratio of shrimp waste powder to glycerol, which resulted in a tensile strength of 19.26 N/mm2, elongation of 84.09%, thickness of 0.35 mm, water absorption of 30.79%, WVTR of 20.80 g/m2.h and a faster decomposition rate compared to synthetic plastics.